2016
DOI: 10.1055/s-0042-100913
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Acromegaly in Patients with Carpal Tunnel Syndrome: A Prospective Study (ACROCARP)

Abstract: Early diagnosis of acromegaly prevents irreversible comorbidities and facilitates surgical cure. Carpal tunnel syndrome (CTS) is common in acromegaly and patients have often undergone surgery for CTS prior to the diagnosis of acromegaly. We hypothesized that screening CTS-patients for acromegaly could facilitate active case-finding. We prospectively enrolled 196 patients [135 women, 56.9 (range 23-103) years] who presented with CTS for surgery. Patients were asked about 6 symptoms suggestive of acromegaly usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Previous studies that screened for acromegaly in the general population [11], and in hypertensive [12], diabetic [3] or carpal tunnel syndrome patients [13] found similar results to ours. In patients with existing comorbidities, the only clinical indicators of acromegaly are obvious facial dysmorphism and enlargement of the extremities.…”
supporting
confidence: 89%
“…Previous studies that screened for acromegaly in the general population [11], and in hypertensive [12], diabetic [3] or carpal tunnel syndrome patients [13] found similar results to ours. In patients with existing comorbidities, the only clinical indicators of acromegaly are obvious facial dysmorphism and enlargement of the extremities.…”
supporting
confidence: 89%
“…Previous studies have reported that approximately four‐fifths of patients with acromegaly have subclinical abnormalities on electrodiagnostic tests, and up to 64% have symptomatic CTS. Although a substantial improvement in symptoms has been seen when the growth hormone levels are diminished, the exact physiopathologic mechanism has not been clarified . An increase in the size of the median nerve or cross‐sectional area has been studied with both magnetic resonance imaging and US .…”
Section: Discussionmentioning
confidence: 99%
“…Although a substantial improvement in symptoms has been seen when the growth hormone levels are diminished, the exact physiopathologic mechanism has not been clarified. [1][2][3]12 An increase in the size of the median nerve or cross-sectional area has been studied with both magnetic resonance imaging and US. 8,12,13 Ultrasound imaging has shown swelling of the nerve proximal to the entrapment site, 7,10 and magnetic resonance imaging has shown increased signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Нельзя не затронуть и фармакоэкономические аспекты, поскольку стоимость лечения осложнений намного превышает затраты на курацию основного заболевания [39]. • карпальным туннельным синдромом (ACROCARP) [50].…”
Section: Abstract: Acromegaly; Diagnostics; Selective Screeningunclassified